2010
DOI: 10.1089/thy.2010.0096
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Resistance to Vitamin D Receptor Activation Is Associated with 24-Hydroxylase Levels But Not theffFokI Polymorphism

Abstract: Background: The vitamin D receptor (VDR) has been studied as a novel target for cancer therapy in many tissue types as VDR ligands decrease cell proliferation in vitro and decrease tumor growth in vivo in sensitive cells. The objective of this study was to analyze the response to VDR agonist therapy in a panel of validated thyroid cancer cells and assess genetic markers predicting sensitivity and resistance to calcitriol and the noncalcemic analog DP006. Methods: Thyroid cancer cell lines were analyzed for VDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…These results are similar to those seen by Sharma et al, who reported that the TPC1 and C643 thyroid cancer cells are sensitive to vitamin D receptor activation and have lower baseline levels of CYP24A1 and CYP27B1 as compared with resistant thyroid cancer cell lines. They also reported that thyroid cancer cells with the FF FokI variant of the VDR were relatively resistant to the effects of 1,25(OH) 2 D 3 (8). What is unknown is whether one can overcome the relative resistance to vitamin D in specific cell lines by administering higher doses of either D 3 or 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These results are similar to those seen by Sharma et al, who reported that the TPC1 and C643 thyroid cancer cells are sensitive to vitamin D receptor activation and have lower baseline levels of CYP24A1 and CYP27B1 as compared with resistant thyroid cancer cell lines. They also reported that thyroid cancer cells with the FF FokI variant of the VDR were relatively resistant to the effects of 1,25(OH) 2 D 3 (8). What is unknown is whether one can overcome the relative resistance to vitamin D in specific cell lines by administering higher doses of either D 3 or 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 98%
“…It is already known that thyroid cells have VDRs and CYP27B1 and CYP24A1 gene expression (8). Additionally, Sharma and colleagues have already reported VDR expression for TPC1, C643, Hth7(8), BCPAP, and KTC1 (16) thyroid cancer cell lines and all cells have VDR expression with Hth7 having the least. The presence of CYP27A1 and CYP2R1 gene expression indicates there is potential for thyroid cells to generate active vitamin D (1,25(OH) 2 D 3 ) in the presence of adequate levels of D 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations